FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN BERAT-KURANG (UNDERWEIGHT) PADA BALITA DI PERKOTAAN DAN PERDESAAN INDONESIA BERDASARKAN DATA RISKESDAS TAHUN 2013 - Ria Helda Pratiwi; Suyatno Suyatno; Ronny Aruben (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2015)
The underweight remains a public health problem to toddlers in Indonesia. The purpose of the study was to identify the factors related to underweight toddler in urban and rural Indonesia. The study uses Riskesdas of Indonesia in year 2013 with the design of cross-sectional study. The total sample 78.535 respondents. Analysis of the data using univariate and bivariate analysis with the chi-square statistical test (p = 0,05). The results showed that underweight toddler higher at the age of 0-23 months both in the urban (41,9%) and rural (46,7%), underweight higher in toddler girl both in the urban (18,9%) and rural (23,1%), underweight todder was higher on the mother’s age at risk to have a toddler underweight both in the urban (18,2%) and rural (21,8%), underweight toddler higher in mother who have low education both in the urban (17,3%) and rural (21,6%), underweight toddler higher in mother does not work both in urban (18,6%) and rural (23,3%), underweight toddler higher in family income poor both in urban (18,6%) and rural (22,3%). Underweight toddler higher who ever had acute respiratory infection disease both in urban (17,5%) and rural (22,5%), diarrhea disease both in urban (15,9%) and rural (18,6%), pulmonary tuberculosis disease both in urban (17,8%) and rural (22,1%). Underweight toddler higher in neonatal visit not complete both in urban (18%) and rural (22,5%), underweight toddler higher in toddler who do weighing irregular both in urban (21,1%) and rural (24,4%), underweight toddler higher in mother who have not Growth Chart Card (KMS) both in urban (22,5%) and rural (25,9%), underweight toddler higher in toddler who did not complete immunization both in urban (21,6%) and rural (25,8%), underweight toddler higher in mother who has not given breastfeeding both in urban (59,9%) and rural (62,3%), underweight toddler higher in mother that give food complement of breast milk to toddler age < 6 months both in urban (39,2%) and rural (43%). The factors related to underweight toddler in urban and rural Indonesia based on data Riskesdas 2013 were genders toddlers, age of mother, employment, family income, acute respiratory infection disease, diarrhea disease, pulmonary tuberculosis, neonatal visits, monitoring of weighing, have a Growth Chart Card (KMS), immunization status, granting breastfeeding, the first ages toddlers given food complement of breast milk (MP-ASI).